Impacts of social capital on housing prices: the case of special relationship-based transactions - Lee, Chun-Chang; Yeh, Wen-Chih; Yu, Zheng; Liang, Chih-Min (International Journal of Strategic Property Management, 2023)
In Taiwan, many housing transactions are special relationship-based transactions that involve family and friends, debt relations, urgent purchases and sales, and government agencies. As such, the prices in such transactions should differ from those in what we consider to be normal arm’s length transactions. In this regard, social capital theory can be used to analyze these transactions. The empirical data on housing transactions conducted in Taipei City from January 1, 2012 to December 31, 2018 were collected for this study. The empirical results showed that the prices in transactions involving debt relations and urgent purchases and sales were 22.6% lower than those in normal arm’s length transactions. The prices in transactions with government agencies were 48.9% lower than those in normal arm’s length transactions. The prices in transactions with first-degree, second-degree, and third-degree relatives were respectively, 57.3%, 53.1%, and 50.3% lower than those in normal arm’s length transactions. The prices in transactions involving friends were 28.0% lower than those in normal arm’s length transactions. The empirical results highlight the importance of the impacts of personal relationships or social relations on housing prices in special relationship-based transactions. The results also supported the social capital hypothesis.